Multivalent SnO2 quantum dot-decorated Ti3C2 MXene for highly sensitive electrochemical detection of Sudan I in food. Issue 23 (7th November 2022) - Mei, Lin; Shi, Yanmei; Shi, Yange; Yan, Pengpeng; Lin, Chunlei; Sun, Yue; Wei, Bingjie; Li, Jing
Abstract : A new electrochemical sensor was fabricated by SnO2 quantum dot-decorated Ti3 C2 MXene for the highly sensitive detection of Sudan I in food. This sensor with good selectivity, precision and accuracy can be used in monitoring illegal food additives. Abstract : Quantum dots functionalization has been proven to be a simple modification strategy for improving the electroanalytical performance of two-dimensional electrode materials by increasing the specific surface area and active reaction sites. Herein, a new electrochemical sensing platform was fabricated by SnO2 quantum dot-functionalized Ti3 C2 MXene (Ti3 C2 -SnO2 QDs) for the highly sensitive detection of Sudan I in food. Ti3 C2 -SnO2 QDs were prepared via in situ synthesis, which can control the nucleation and growth of SnO2 QDs, resulting in the well-dispersed SnO2 QDs with 2–3 nm size on the intersheet surface of MXene. Moreover, the formation of Ti3 C2 -SnO2 QDs can effectively restrict the aggregation of Ti3 C2 and improve the stability of SnO2 QDs in aquatic environment. The prepared nanocomposite can be used as an improved modified material to further increase the electrocatalytic performance and electrochemical signal of Sudan I on the surface of a glassy carbon electrode. Under optimized conditions, the proposed analytical method displayed a linear dependence for Sudan I concentration ranging from 0.008 to 10 μM with a detection limit of 0.27 nM (S/N = 3) by electrochemical cyclic voltammetry. This sensor with excellent selectivity, reproducibility and accuracy was quantitatively validated in commercial ketchup and chili powder. This Ti3 C2 -SnO2 QDs-based Sudan I sensor is expected to expand the application of MXene nanocomposites in electrochemical analysis and is envisioned as a promising candidate for monitoring illegal food additives in real food samples.